Identification of a new genetic site (sac-3+) in Neisseria gonorrhoeae that affects sensitivity to normal human serum. - Shafer, W M (1982)
A previously undescribed genetic site (sac-3) affecting susceptibility of the gonococcus to normal human serum was localized on the gonococcal chromosome. The presence of the sac-3+ allele in a clinical isolate (FA889) resulted in sensitivity only to relatively high concentrations of serum (greater than or equal to 12.5%). Genetic mapping experiments demonstrated that sac-3+ was tightly linked to another genetic site (sac-1+) involved in determining susceptibility to normal human serum and to a locus (nmp-3) involved in the replacement of outer membrane protein I. The sac-1+ and sac-3+ loci resulted in phenotypically distinct levels of sensitivity to human serum. The sac-3+ serum sensitivity and sac-1+ serum sensitivity loci recombined with high frequency, resulting in serum resistance. The results show that serum sensitivity in clinical isolates may be due to different serum sensitivity loci and suggest that different antigens and immunological mechanisms could be responsible for sensitivity of different gonococcal isolates to human serum.